Dietary Soybean Oil Supplementation Affects Keel Bone Characters and Daily Feed Intake but Not Egg Production and Quality in Laying Hens Housed in Furnished Cages - Wei, Haidong; Pan, Lei; Li, Chun; Zhao, Peng; Li, Jianhong; Zhang, Runxiang; Bao, Jun (Frontiers in Veterinary Science, 2021)
To evaluate dietary soybean oil supplementation on production performance, egg quality, and keel bone health in laying hens. 204 laying hens at 20 weeks of age (WOA) were distributed into twelve cages containing 17 birds each. Birds were either fed a commercial diet (control group, CON) or a diet supplemented with 3% of soybean oil (SO group). Experiments lasted seventeen weeks. Body weight, daily feed intake, production performance and egg quality were measured at 25, 29, 33, and 37 WOA. Birds were subsequently assessed for keel bone status by palpation, and keel was excised to measure bone length, microstructure, bone mineral density (BMD), elements contents, and the expression of osteoprotegerin (OPG), receptor activator of nuclear factor kappa-B ligand (RANKL), collagen type II alpha 1 (COL2α1), periostin (POSTN), and sclerostin (SOST). The results showed that dietary SO supplementation did not affect production performance and egg quality (P > 0.05), but improved body weight of hens at 29 and 37 WOA (P < 0.05), and decreased daily feed intake at 33 and 37 WOA (P < 0.05). Incidence of keel bone damage (especially fracture) was higher in hens of SO group. Keel bone length in birds of SO group was significantly decreased compared to CON (P < 0.05). Keel bone of supplemented hens showed increased trabecular separation at 29 WOA and higher levels of V, Mn, Fe, Se, and Ba at 33 WOA (P < 0.05). Moreover, decreased BMD, trabecular number and thickness were observed in keel bone of laying hens receiving supplementation at 29 and 37 WOA (P < 0.05); decreased levels of Li, Ca, Hg, and TI at 33 WOA and trabecular thickness at 37 WOA (P < 0.05) were also identified. mRNA levels of SOST and RANKL and the ratio of RANKL/OPG mRNA levels were increased in birds fed a SO-supplemented diet (P < 0.05); COL2α1, OPG, and POSTN were downregulated at all sampling points (P < 0.05). Taken together, results indicate that feeding laying hens a diet supplemented with SO can decrease daily feed intake and impair keel bone health but not influence production performance and egg quality.